Iodine-catalyzed cross-coupling of isocyanides and thiols for the synthesis of S-thiocarbamates. Issue 37 (12th September 2018) - Pathare, Ramdas S.; Patil, Vikas; Kaur, Harpreet; Maurya, Antim K.; Agnihotri, Vijai K.; Khan, Shahnawaz; Devunuri, Nagaraju; Sharon, Ashoke; Sawant, Devesh M.
Abstract : Synthesis of S -thiocarbamates by employing simple and readily available precursors under mild reaction conditions with good to excellent yields. Abstract : A novel and efficient metal free, redox-neutral method for the synthesis of secondary thiocarbamates by cross-coupling of readily available thiophenol and isocyanides has been developed. The present methodology exhibits a broad substrate scope with good to excellent yields without an additive/extra oxidant under mild reaction conditions catalyzed by inexpensive iodine as the catalyst.